2018
DOI: 10.1007/s10457-018-0270-2
|View full text |Cite
|
Sign up to set email alerts
|

GIS approach to estimate windbreak crop yield effects in Kansas–Nebraska

Abstract: Windbreaks were originally promoted across the U.S. Great Plains to reduce wind erosion. A review paper published nearly 30 years ago showed yield increases for a variety of crops associated with windbreaks. However, with the widespread use of notill cropping systems and advanced crop genetics, the question is ''Do windbreaks still provide a yield benefit?'' This study compared data from protected and unprotected fields over multiple years across Kansas and Nebraska looking at relative soybean (Glycine max L.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…It is estimated that about 1.9 billion hectares of land and 250 million people are currently affected by desertification worldwide [1]. In response to the threat, many countries have implemented desertification control projects (DCPs), such as the Prairie States Forestry Project in the United States and the Spanish National Action Programme to Combat Desertification in Europe [2,3]. The United Nations Convention to Combat Desertification (UNCCD) came into force in 1996, and proposed a new sustainable development goal for Rio+20-zero net land degradation by 2030 [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that about 1.9 billion hectares of land and 250 million people are currently affected by desertification worldwide [1]. In response to the threat, many countries have implemented desertification control projects (DCPs), such as the Prairie States Forestry Project in the United States and the Spanish National Action Programme to Combat Desertification in Europe [2,3]. The United Nations Convention to Combat Desertification (UNCCD) came into force in 1996, and proposed a new sustainable development goal for Rio+20-zero net land degradation by 2030 [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, riparian buffers could be established entirely on cropland or to a varying degree on existing, unmanaged, buffers, thus limiting the reduction in cropland area. In the former case, agricultural production will initially decrease, but if yield levels increase on the cropland areas that benefit from reduced erosion or flooding mitigation (Li et al, 2016;Osorio et al, 2019), this could more or less outweigh the negative effect of reduced cropland area. For windbreaks, significant parts of the agricultural landscape are converted from annual crops (1/3 for SRC windbreaks and 1/9 for SRF windbreaks at 100% implementation) in the different scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…They are also likely to enhance SOC, if established on land historically used for annual crop production, enhance conditions for biodiversity by, e.g., improving landscape connectivity, and protect agricultural fields from wind and water erosion (Englund et al, 2020a). Windbreaks are strips of woody crops, such as poplar or willow, located within or between fields to protect agricultural land from wind erosion (Osorio et al 2019). Similar to riparian buffers, multifunctional windbreaks may lead to co-benefits such as enhanced SOC and reduced nutrient leaching (Englund et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the favorable microclimate conditions provided by shelterbelts, crop yields can increase 10−30% (Cao 1983;Brandle et al 2004;Iwasaki et al 2019). Although a few studies on the effects of shelterbelts on microclimates and crop yields at Jiang et al 2003) landscape levels have been conducted (Deng et al 2011;Osorio et al 2019), by Zheng et al (2016), the influence of the protection levels on crop yields in different climatic productivity zones at a landscape scale had been quantified. They reported that maize yields increased steadily as levels of protection increased up to 80%, and decreased thereafter in zones with high and middle climatic potential productivity.…”
Section: Quantitative Structures Of Shelterbelts and Their Relationshmentioning
confidence: 99%